Insuficiencia del código orgánico integral penal en los criterios de valoración de las pruebas en la resolución de los procesos penales - Salazar Ulloa, Nathaly Alexandra (2016)
Throughout the social development of man within the social sphere and as a means of ordering of its surroundings, was obliged to establish the rules of behavior or social performance, complying with keeping order and social peace, on the basis of a set of rules that regulated by principles, guarantees, rights and obligations. The organic comprehensive Criminal Code establishes some assessment criteria, which are determined in the Art.457 in the following way "The test will be taking into account its legality, authenticity, subjection to chain of custody and current degree of scientific and technical acceptance of the principles that expert reports are based. Demonstration of the authenticity of the evidence and physical evidence not subjected to chain of custody, will be in charge of the party presenting them In the search for that truth in the process, the judge has at its disposal evidentiary means, that according to our legal system its valuation governing legality, authenticity, subjection to chain of custody and current degree of scientific and technical acceptance of the principles that expert reports are based, but there is no mention that the judge should be governed for the assessment of the tests as well as the healthy criticism Therefore, our criminal procedure in terms of the resolution, by the Commission of a crime, must substantiate in ventilation and legality of evidence reproduced in the criminal process, so the judge who knows the cause should apply sound critique as method of valuation of these. Criticizes the healthy method consists in considering a set of judges criteria standards, based on logic, experience and psychology, and even common-sense guidelines that coupled with lead to the human belief. The Sana'a criticizes rules are integrated, on the one hand with the fundamental principles of the human intellect, pillars of all rational knowledge and instrument of certainty, on their way to the logical and ontological truth, and on the other hand the maximum experiences called rules of thumb. The problem lies, in limitation that must have that application, since what some jurists is right for others, because is not to judge great power or faculty so that it can meet its discretion. That freedom given by the Sana Critica, recognizes a limit which is the respect for the rules governing the correction of thought, i.e. the laws of logic, psychology and common experience, so it is required that the conclusions that they arrive are the rational result of tests of the process, without involvement of the logical principle of sufficient reason , which requires proof that melts only allow to arrive to a conclusion and not to another, must be not only respected those principles but also of identity and contradiction, excluded Hence the need for a reform to the Penal organic code Integral application of healthy criticism in the resolution of criminal proceedings, so determine the Faculty of sound criticism of the judges in the assessment of evidence and with this safeguard respect for and compliance with the principles rights and guarantees criminal.